2020
DOI: 10.1177/1756284820959183
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab and liver injury in patients with COVID-19

Abstract: Current mortality rate in patients with COVID-19 disease is about 2%, whereas 5% of patients require admission to the intensive care unit. It is assumed that interleukin (IL)-6 may be involved in the pathogenesis of severe COVID-19 infections; therefore, in the absence of a specific antiviral therapy, some authors have suggested that tocilizumab – a drug used to block the signal transduction pathway of IL-6 – could have beneficial effects in the management of severe COVID-19 disease. However, mild-to-moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 33 publications
1
38
0
4
Order By: Relevance
“…One of the female patients had a mild increase in ALT and AST levels two days post-administration of the drug which quickly normalized, whereas the male initially had mildly elevated liver function tests that did not further increase post-tocilizumab therapy [93]. Similarly, the study by Serviddio et al reported normalization in transaminases levels, 3 weeks after tocilizumab administration in seven cases of patients with baseline values up to 5 times the upper limit of normal [94]. Therefore, further studies are warranted in examining the effect of tocilizumab administration on liver function tests in severe COVID-19 patients with pre-existing chronic hepatic diseases.…”
Section: Tocilizumabmentioning
confidence: 85%
“…One of the female patients had a mild increase in ALT and AST levels two days post-administration of the drug which quickly normalized, whereas the male initially had mildly elevated liver function tests that did not further increase post-tocilizumab therapy [93]. Similarly, the study by Serviddio et al reported normalization in transaminases levels, 3 weeks after tocilizumab administration in seven cases of patients with baseline values up to 5 times the upper limit of normal [94]. Therefore, further studies are warranted in examining the effect of tocilizumab administration on liver function tests in severe COVID-19 patients with pre-existing chronic hepatic diseases.…”
Section: Tocilizumabmentioning
confidence: 85%
“…It is possible that younger patients mount a more robust immune and inflammatory response to infection, and that higher peak SGPT is a manifestation of it [12]. Role of immunomodulators like tocilizumab in cases of ALF in COVID-19 patients has been investigated with adult patients showing improvement but its role in pediatric patients should be investigated [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Qin et al [ 37 ] reported that up to 70% of critically ill patients received systemic corticosteroid therapy. Furthermore, a case report from Italy suggested that tocilizumab, a drug used to reduce inflammation by blocking the IL-6 signal transduction pathway, played a beneficial role in the management of severe COVID-19 disease[ 59 ]. In the case of poor efficacy of azithromycin, hydroxychloroquine, and lopinavir, the administration of tocilizumab rapidly improved the clinical condition.…”
Section: Potential Mechanisms Of Liver Injury In Patients With Covid-19mentioning
confidence: 99%